2019
DOI: 10.1088/1361-6501/ab0c5b
|View full text |Cite
|
Sign up to set email alerts
|

A robust calibration technique for concentration measurements using ionisation detectors

Abstract: Accurate calibration procedure is essential to obtain reliable concentration measurements using ionisation-based sensors. Existing methods assume linear behaviour of ionisation sensors and do not account for errors that arise due to sensor drift, changes in ambient conditions, etc. In this paper, we implement a robust calibration procedure to account for most forms of drift that are typically noticed during concentration measurements using ionisation detectors. The method involves calibrating the sensor before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The spanwise gap between the two PIDs is approximately 3 mm, in accordance with the results of [15], who showed that a PID has negligible influence on an adjacent probe when separated by a distance greater than 3d, where d = 0.76 mm is the inlet diameter of PID probes used in this study. Details of calibration procedure, spatial resolution and frequency response of PID are also given in [21,23]. Although the experimental test-rig and the measurement procedures used in this study are similar to that of [20], the present study is distinct and reports simultaneous measurements of concentration at two points in the plume.…”
Section: B Meandering Of a Slender Passive Scalar Plumementioning
confidence: 99%
“…The spanwise gap between the two PIDs is approximately 3 mm, in accordance with the results of [15], who showed that a PID has negligible influence on an adjacent probe when separated by a distance greater than 3d, where d = 0.76 mm is the inlet diameter of PID probes used in this study. Details of calibration procedure, spatial resolution and frequency response of PID are also given in [21,23]. Although the experimental test-rig and the measurement procedures used in this study are similar to that of [20], the present study is distinct and reports simultaneous measurements of concentration at two points in the plume.…”
Section: B Meandering Of a Slender Passive Scalar Plumementioning
confidence: 99%